2019
DOI: 10.1002/srin.201800500
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of the Recrystallization Behavior of Low Alloyed Steels

Abstract: The recrystallization behavior of five low alloyed steels is investigated using double hit deformation tests. It is shown, that Niobium has the biggest influence in retarding the recrystallization kinetics. Further, the microstructural evolution dependent on strain and temperature during deformation is studied with a picric acid etchant and light-optical analysis. It is shown how the microstructure of two differently alloyed ultra-high strength steels changes along with the peculiarities of the corresponding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Vervynckt et al [9] also examined the influence of different levels of Nb-microalloying on the SRX kinetics in low-carbon steels at 900 • C, and according to their study, 0.02% Nb alloying caused delay in the SRX kinetics only due to the solute drag effect, whereas a higher Nb alloying (0.04-0.16% Nb) resulted in both precipitation as well as the solute drag effect, respectively. The hindering effect of V and Nb on SRX kinetics in low alloy steels was also reported by Esterl et al [10]. Pereda et al [11] concluded that increasing Mo content in 0.05C-Nb steels increased the T nr essentially due to an enhanced solute drag effect in steels with low Nb content (0.03% Nb), whereas in steels with relatively higher Nb content (0.06% Nb), the acceleration of strain induced precipitation became more relevant than the solute drag.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Vervynckt et al [9] also examined the influence of different levels of Nb-microalloying on the SRX kinetics in low-carbon steels at 900 • C, and according to their study, 0.02% Nb alloying caused delay in the SRX kinetics only due to the solute drag effect, whereas a higher Nb alloying (0.04-0.16% Nb) resulted in both precipitation as well as the solute drag effect, respectively. The hindering effect of V and Nb on SRX kinetics in low alloy steels was also reported by Esterl et al [10]. Pereda et al [11] concluded that increasing Mo content in 0.05C-Nb steels increased the T nr essentially due to an enhanced solute drag effect in steels with low Nb content (0.03% Nb), whereas in steels with relatively higher Nb content (0.06% Nb), the acceleration of strain induced precipitation became more relevant than the solute drag.…”
Section: Introductionsupporting
confidence: 78%
“…The SRX kinetics of hot deformed austenite in C-Mn steels (with Mn < 1.5%, Si < 0.25%; hereinafter, all concentrations are in wt.%) as a function of chemical composition including the effects of V, Ti and Nb have been reported by numerous authors, for example, [6][7][8][9][10][11][12]. Medina and Quispe [13] have published experimental recrystallization-precipitation-timetemperature diagrams for various V and Nb microalloyed steels illustrating the start and finish temperatures of SRX as well as precipitation at different temperatures.…”
Section: Introductionmentioning
confidence: 95%
“…The results of this work coincide well with the results of other research groups, which have described similar recrystallization behavior for different HSLA steels in the past. [17,18,20] Particularly, in this work, it was shown that the annealing temperature before deformation is decisive for an increased recrystallization-inhibiting effect of Nb-and Ti-alloyed HSLA steels. Annealing temperatures below the equilibrium solution temperature of Nb(C,N) do not ensure sufficient dissolution of Nb and, thus prevent the formation of strain-induced precipitates after deformation.…”
Section: Discussionmentioning
confidence: 72%
“…[1,16] In the past, several studies have shown that strain-induced precipitations inhibit static recrystallization, which can be seen in a deviation from Avrami-like behavior, i.e., the formation of a plateau in a recrystallization curve. [17][18][19][20] An understanding of the precipitation behavior of the microalloying elements is therefore essential for controlling the thermomechanical rolling processes.…”
mentioning
confidence: 99%
“…The second base alloy, contains an elevated amount of Cr (0.7%), which increases hardenability and enhances temper resistance . In addition, Cr acts as grain refiner, whereas its influence on recrystallization during hot rolling is negligible . The modifications of base alloy 2 are alloyed with amounts of ≈0.1% and ≈0.2% V to compare the microstructural processes during hot rolling and after tempering to the Nb variants of base alloy 1.…”
Section: Methodsmentioning
confidence: 99%